2023
DOI: 10.2147/ijgm.s435598
|View full text |Cite
|
Sign up to set email alerts
|

Association Between ALDH2 Polymorphisms and the Risk of Diabetes Mellitus in Hypertensive Patients

Miao Zeng,
Yiping Liu,
Yunquan Xie

Abstract: Background Aldehyde dehydrogenase 2 ( ALDH2 ) polymorphisms have been extensively studied in patients with hypertension (HTN) and diabetes mellitus (DM) in recent years. However, it is unclear whether ALDH2 polymorphisms are correlated with the risk of developing DM in patients with HTN. This study was designed to examine the association between ALDH2 single nucleotide polymorphism (SNP) rs671 and the risks of DM in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Previous studies report that ALDH2 deficiency increases oxidative stress in the body and is a susceptibility factor for hypertension ( Tanaka et al, 2023 ). Some previous studies have also found that tALDH2 plays an important role in cardiovascular and nervous systems, tumors, and other diseases and is an important target for preventing and intervening in cardiovascular diseases ( Zeng et al, 2023 ). Immune cell infiltration indicates that the ALDH2 gene is correlated with various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report that ALDH2 deficiency increases oxidative stress in the body and is a susceptibility factor for hypertension ( Tanaka et al, 2023 ). Some previous studies have also found that tALDH2 plays an important role in cardiovascular and nervous systems, tumors, and other diseases and is an important target for preventing and intervening in cardiovascular diseases ( Zeng et al, 2023 ). Immune cell infiltration indicates that the ALDH2 gene is correlated with various immune cells.…”
Section: Discussionmentioning
confidence: 99%